The frequency and sources of homework in science and social studies in Croatia and Slovenia - Borić, Edita (Array, 2021)
Just as each school subject has its own specific goals, so the role of homework depends on the specific requirements and learning outcomes of the subject within which it is assigned. Homework in Science and Social Studies should be assigned in those parts of learning content that will require research-oriented and problem-solving activities, which will enable students to gain experience, develop creativity and apply knowledge and skills in everyday life. The study included primary school teachers in Croatia and Slovenia (N = 144). The observation was conducted in real-life situations during Science and Social Studies lessons. The results show that Croatian teachers assign statistically significantly more homework and use ready-made sources of homework assignments more than Slovenian teachers. Teachers of both countries have preferences towards workbooks as the most commonly used source of homework. The aim of the paper is to emphasize the need for reducing homework in the Croatian practice. It also sheds light on the role of the teacher in designing homework tasks that will not be automatically assigned, but will have a meaningful purpose and be oriented towards students’ needs and interests while developing their competencies.